The impact of land use and land cover change on biodiversity within and adjacent to Kibasira Swamp in Kilombero Valley, Tanzania. (23rd November 2017) - Seki, Hamidu A.; Shirima, Deo D.; Courtney Mustaphi, Colin J.; Marchant, Rob; Munishi, Pantaleo K. T.
Abstract: Wetlands are crucial ecosystems with multiple values and functions to a range of different stakeholders. The future of wetlands depends both on the legacy of the past and how they are currently used. Using 48 vegetation survey plots (0.08 ha) combined with Landsat 5 and 7 TM imagery, we assessed the influence of long‐term (1990–2011) land use and land cover change on the biodiversity of the Kibasira Swamp. Information on perceptions of adjacent communities on historical changes and drivers for the changes were also collected. Results showed an increase in the area covered by open water by 1% and forest by 4% between 1990 and 1998 whilst Cyperus papyrus L and cultivated land area decreased by 8% and 3%, respectively on the same period. Between 1998 and 2011, there was a decrease in areas covered by water by 35% and forest by 9% whereas C. papyrus L increased by 40% and cultivated land increased by 8%. These changes have affected the biodiversity of the swamp and adjacent to it as numbers of mammals have declined. However, the Swamp still provides extensive habitat for plants and bird species despite the ongoing human pressure. Interventions may be necessary to maintain biodiversity in Kibasira Swamp to ensure sustainable ecosystem services.